2013
DOI: 10.1038/ncomms2435
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of the vesicular stomatitis virus nucleocapsid into a bullet shape

Abstract: The typical bullet shape of Rhabdoviruses is thought to rely on the matrix protein for stabilizing the nucleocapsid coil. Here we scrutinize the morphology of purified and recombinant nucleocapsids of vesicular stomatitis virus in vitro. We elucidate pH and ionic strength conditions for their folding into conical tips and further growth into whole bullets, and provide cryo-electron microscopy reconstructions of the bullet tip and the helical trunk. We address conformational variability of the reconstituted nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Recent work has shown that N-RNA alone can adopt the classic bullet shape of the interior of the virion (43). This raises the possibility that the particles stuck at the membrane are viral particles that lack significant M. Earlier in vitro dissociation and reassociation experiments with NCM complexes proposed that the association of the RNP with a minor virion component mediates conversion to the NCM complex (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that N-RNA alone can adopt the classic bullet shape of the interior of the virion (43). This raises the possibility that the particles stuck at the membrane are viral particles that lack significant M. Earlier in vitro dissociation and reassociation experiments with NCM complexes proposed that the association of the RNP with a minor virion component mediates conversion to the NCM complex (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In the virion, the N-RNA complex comprising 12 kb RNA and approximately 1300 N protomers is present in a highly condensed superhelical form and associated with approximately 650 copies of P protein dimers, which bind between two adjacent N molecules, and 50 molecules of the large RNA polymerase subunit L. The superhelix is surrounded by an envelope comprising a continuous inner M protein mesh, a lipid membrane, and trimers of the transmembrane glycoprotein G. The overall shape of the virion is imposed by the M protein layer, which determines the number of N subunits per turn, the diameter of the trunk, and the pitch of the RNP superhelix (Green et al, 2006). As described for VSV, the conical end is a consequence of N-RNA helix self-assembly and comprises the 5 -end of the viral RNP genome (Albertini et al, 2006;Desfosses et al, 2013;Green et al, 2006;Luo et al, 2007).…”
Section: Rabies Virionsmentioning
confidence: 99%
“…In vesicular stomatitis virus (VSV) of the Rhabdoviridae family, NC also forms a left-handed helix when packaged in the virion (19). When isolated from the virion, however, VSV NC does not retain a helical structure, although the vRNA is still sequestered in the nucleocapsid, according to the crystal structure of the VSV NLP (12,20). It has been shown that the C-terminal domain of VSV P (P CTD ) binds at the interface of two CTDs from neighboring parallel N subunits (21).…”
mentioning
confidence: 99%